Plasma nitriding without formation of compound layer for 38CrMoAl hydraulic plunger. (September 2017) - Chen, Yao; Song, Lei; Zhang, Chenkai; Ye, Xuemei; Song, Renguo; Wang, Zhixiu; Zhao, Xiaobing; Hu, Jing
Abstract: In this study, low temperature plasma nitriding (LPN) was primarily used in 38CrMoAl hydraulic plunger to overcome the peeling problem of the compound layer in real application. The cross-sectional microstructures of the treated samples were observed by optical metallography, phase constituents were determined by X-ray diffraction (XRD), the microhardness profile and brittleness of surface were measured by microhardness tester. The results showed that no compound layer was formed while plasma nitriding at 450 °Cfor 6 h, and XRD also confirmed that there existed no γ′-Fe4 N. Meanwhile, the brittleness was decreased at lower temperature plasma nitriding comparing with normal plasma nitriding (NPN), due to no brittle compound layer formed on the outmost layer. Highlights: The low temperature plasma nitriding can enhance the production efficiency of the 38CrMoAl hydraulic plunger.